2003
DOI: 10.1023/a:1023958324448
|View full text |Cite
|
Sign up to set email alerts
|

EGFR, HER-2/neu, Cyclin D1, p21 and p53 in Correlation to Cell Proliferation and Steroid Hormone Receptor Status in Ductal Carcinoma in situ of the Breast

Abstract: Abnormalities in G1/S transition in cell cultures have been attributed to alterations in ErbB (erythroblastic leukaemia viral [v-erb-b] oncogene homologue, avian) signalling, cyclin D1 overexpression or disturbance of the p21(WAF1) (p21)-mediated cell cycle arrest induced by p53. To investigate the significance of these mechanisms on an early stage of human breast tumour growth, we studied the expression of EGFR (ErbB1), HER-2/neu (ErbB2), cyclin D1, p21 and p53 as well as oestrogen (ER) and progesterone recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
0
9

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(78 citation statements)
references
References 55 publications
5
64
0
9
Order By: Relevance
“…In contrast, overexpression of the mitogenic signalling mediator EGFR, indicative of abnormalities in the commitment of G1 to S phase in the cell cycle, was found in 30% of breast lesions, predominantly in invasive carcinoma (53%). Similar rates of EGFR overexpression have been reported previously in DCIS and invasive carcinoma (Knoop et al, 2001;Lebeau et al, 2003). The causes of EGFR overexpression are not well understood but aneusomy of chromosome 7 on which the EGFR gene is located does not relate directly to EGFR protein overexpression (Bhargava et al, 2005;Sauer et al, 2005).…”
Section: Upper Row (Hande) Cancer (A and D) Dcis (B) And Hyperplasia supporting
confidence: 78%
“…In contrast, overexpression of the mitogenic signalling mediator EGFR, indicative of abnormalities in the commitment of G1 to S phase in the cell cycle, was found in 30% of breast lesions, predominantly in invasive carcinoma (53%). Similar rates of EGFR overexpression have been reported previously in DCIS and invasive carcinoma (Knoop et al, 2001;Lebeau et al, 2003). The causes of EGFR overexpression are not well understood but aneusomy of chromosome 7 on which the EGFR gene is located does not relate directly to EGFR protein overexpression (Bhargava et al, 2005;Sauer et al, 2005).…”
Section: Upper Row (Hande) Cancer (A and D) Dcis (B) And Hyperplasia supporting
confidence: 78%
“…p53 mutations/accumulation are present in a significant percentage of DCIS cases (Lebeau et al 2003;Poller et al 1993), especially in the comedo type (O'Malley et al 1994). However, the clinical significance of p53 accumulation remains still elusive; although it has been found to influence the proliferation rate (Rudas et al 1997), a recent study showed that it does not affect the proliferation rate of the DCIS lesion per se (Lebeau et al 2003).…”
Section: P53mentioning
confidence: 99%
“…However, the clinical significance of p53 accumulation remains still elusive; although it has been found to influence the proliferation rate (Rudas et al 1997), a recent study showed that it does not affect the proliferation rate of the DCIS lesion per se (Lebeau et al 2003). Is worth noting that the coexistence of DCIS with IDC is not associated with a different degree of p53 immunostaining (Myonlas et al 2005).…”
Section: P53mentioning
confidence: 99%
See 1 more Smart Citation
“…Breast tumors that are PR(-) have a much higher proliferation rate and are more likely to manifest increased expression of the tumorigenic prognostic indicators, HER-2/neu and EGFR, than PR(+) tumors [56][57][58][59]. PR exists as three major isoforms, PR-A (94 kDa), PR-B (114 kDa) [60] and PR-C (60 kDa) [61].…”
Section: Pr and Breast Cancermentioning
confidence: 99%